2008
DOI: 10.1167/8.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Rebounding V1 activity and a new visual aftereffect

Abstract: A serendipitous observation led to this study of V1 activity rebounds, which occur well after stimulus offset, and their relationship to visual aftereffects. We found that when a stimulus bar and background were simultaneously turned off, there was strong delayed rebounding activity (distinct from any off response). The neural rebound started 350-500 ms after stimulus offset, and its magnitude and duration were correlated with the prior visual response of the cell. In human psychophysical experiments, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Previous studies have shown that brief stimulus presentations at high contrast produce strong persistent activity in primary visual cortex (Funayama et al, 2015;Huang et al, 2008). In our data, the flashed visual stimulus evoked a biphasic population response (example in Figure 1A), with an initial transient component which started immediately after stimulus onset and a delayed reverberatory component which started ~200 ms after stimulus offset.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Previous studies have shown that brief stimulus presentations at high contrast produce strong persistent activity in primary visual cortex (Funayama et al, 2015;Huang et al, 2008). In our data, the flashed visual stimulus evoked a biphasic population response (example in Figure 1A), with an initial transient component which started immediately after stimulus onset and a delayed reverberatory component which started ~200 ms after stimulus offset.…”
Section: Resultssupporting
confidence: 70%
“…Moreover, the influence had behavioral consequences: in a psychophysics task in which human subjects were asked to report the direction of motion of a drifting grating, their response latencies were modulated by a preceding matching or non-matching grating flash, presented 0.5 seconds earlier (Funayama et al, 2015). In a separate study, a simultaneous change in both stimulus and background gave rise to delayed activity in macaque V1 (Huang et al, 2008). The magnitude of the delayed response varied with the size of the background and was strongly correlated with the perception of a visual aftereffect (~300 ms post-stimulus) demonstrated through human psychophysics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In V1, rebound activity is also observed. Here responses leading to rebound activity are feature selective having similar orientation selectivity as the visual response (Huang, Levine, & Paradiso, 2008;). In our model, feed-forward excitation and surround inhibition are also feature specific.…”
Section: Filling-in At Early Visual Stages By Rebound Activitymentioning
confidence: 99%